2022
DOI: 10.1021/acs.analchem.1c04659
|View full text |Cite
|
Sign up to set email alerts
|

Benzoyl Transfer for Footprinting Alcohol-Containing Residues in Higher Order Structural Applications of Mass-Spectrometry-Based Proteomics

Abstract: Protein footprinting mass spectrometry (MS), an emerging approach to elucidate higher-order structure (HOS) and binding, benefits from the iterative development of reaction strategies to expand the covalent labeling toolbox. Herein, we introduce a footprinting reagent for nucleophiles and demonstrate its efficacy for differential covalent labeling MS analysis. Benzoyl fluoride (BF), although reactive with water, is more practical for modifying nucleophilic functional groups than other acid halides and serves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 26 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…BF is found to be more reactive with Lys and Tyr when compared to DEPC, but it is less reactive with Cys (Figure 4). As reported previously, 29 BF modifies hydroxyl-containing tyrosine at a rate ∼10 times greater than DEPC. The modification extent of each peptide failed to reach 100% at all footprinting reagent concentrations (i.e., there are still unmodified cyclic peptides remaining after incubation with the highest concentration of BF and DEPC).…”
Section: ■ Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…BF is found to be more reactive with Lys and Tyr when compared to DEPC, but it is less reactive with Cys (Figure 4). As reported previously, 29 BF modifies hydroxyl-containing tyrosine at a rate ∼10 times greater than DEPC. The modification extent of each peptide failed to reach 100% at all footprinting reagent concentrations (i.e., there are still unmodified cyclic peptides remaining after incubation with the highest concentration of BF and DEPC).…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…We have recently shown that BF-labeled tryptic and chymotryptic peptides undergo significant shifts in LC elution time owing to increases in hydrophobicity, and this phenomenon is recapitulated with these cyclopeptides. 29 Cyclopeptides with two adjacent nucleophilic residues, c(RADYC) and c(RADYK), yielded two peaks of m/z values corresponding to single and double additions of BF. MS/MS analysis of these doubly benzoylated peptides confirms Tyr, Lys, and Cys modification (Figure S4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The reagents utilized in these workflows and hence amino acid selectivity, reaction rates, and necessary considerations can vary widely. ,, , A concern of many labeling-based technologies is the influence derivatization has on the conformation of the protein. This is especially pertinent with these technologies, as many implementations generate multiply derivatized species and utilize reaction durations in the second to minute time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Protein footprinting mass spectrometry (MS) is an analytical tool used for higher order structure (HOS) determination. , Footprinting reagents impart covalent modifications, thereby increasing protein mass, as a function of solvent accessible surface area (SASA). Specific amino acid reagents used for footprinting are generally irreversible and modify side chains, allowing for specificity for certain amino acids (e.g., methylglyoxal for Arg , and glycine ethyl ester for acidic residues Asp/Glu) or more general functional groups (e.g., benzoyl fluoride or diethyl pyrocarbonate for nucleophiles, such as the amine, thiol, hydroxyl, and carboxylate groups of amino acid side chains). This approach is also commonly referred to as covalent labeling MS (CL-MS).…”
mentioning
confidence: 99%